2016
DOI: 10.1016/j.ijmyco.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the GenoType MTBDRplus assay for detection of rifampicin- and isoniazid-resistant Mycobacterium tuberculosis isolates in central Ethiopia

Abstract: The findings of this study revealed that the GenoType MTBDRplus assay has high sensitivity and specificity for the detection of RIF and INH resistance. These preliminary data support the notion that the assay should be considered as an alternative to the DST for the characterization of MDR in M. tuberculosis isolates and the control of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 19 publications
10
54
4
Order By: Relevance
“…On the other hand, mutations in the rpoB gene conferring Rifampicin resistance were present in only 1.1% (1/92) of isolates. A similar trend where Rifampicin resistance was found at rpoB gene S531Lb y Bedewi et al (2016). In this study, Euro American Lineage was associated with resistance to the first line anti-TB drugs, which is agreed with the earlier report in Ethiopia (Bedewi et al, 2017)and in Papua New Guinea (Ballif et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, mutations in the rpoB gene conferring Rifampicin resistance were present in only 1.1% (1/92) of isolates. A similar trend where Rifampicin resistance was found at rpoB gene S531Lb y Bedewi et al (2016). In this study, Euro American Lineage was associated with resistance to the first line anti-TB drugs, which is agreed with the earlier report in Ethiopia (Bedewi et al, 2017)and in Papua New Guinea (Ballif et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…However, performance of genotypic/molecular DST has been shown to be comparable with that of phenotypic DST and is unlikely to be a major factor. [16,17,[43][44][45] We did not analyse second-line resistance and some of these isolates might have demonstrated resistance to second-line drugs, which would render them XDR-TB rather than MDR-TB isolates. Further research in this regard is recommended.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Currently, several molecular DST assays, such as the AdvanSure MDR-TB GenoBlot assay kit (LG Chem, Seoul, Korea) and GenoType MTBDRplus, are clinically used. Both kits demonstrated good performance for MDR-MTB detection in clinical isolates, with concordance rates of 94.3% and 88.5-98.2% [10][11][12], respectively. One study reported that the results of GenoType MTBDRsl, a kit for XDR-MTB detection, showed a concordance rate of 94.7% [13].…”
Section: Discussionmentioning
confidence: 99%